2016
DOI: 10.1177/1535370216638773
|View full text |Cite
|
Sign up to set email alerts
|

Citicoline retards myopia progression following form deprivation in guinea pigs

Abstract: The retinal dopaminergic system is involved in the myopic shift following form deprivation. Citicoline has been demonstrated to stimulate the dopaminergic system in the brain and retina. Furthermore, citicoline has been used in many neurogenic diseases, such as senile cognitive impairment, stroke and Parkinson's disease as well as in amblyopia and glaucoma. Our aim was to investigate the effect of citicoline on the refractive state and retinal dopamine level in form deprivation myopia of guinea pigs. Guinea pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 37 publications
1
18
0
1
Order By: Relevance
“…The findings of the present study, which are supported by observations made in a previous investigation, may suggest that EGF and members of the EGFR family, such as amphiregulin, are some of the substances that were positively or negatively associated with the development of experimental myopia in previous studies. These substances include dopamine, acetylcholine, and other molecules from the cholinergic system and GABAergic system, insulin, glucagon, glucagon‐like peptide‐1, basic fibroblast growth factor, transforming growth factor beta, vasoactive intestinal polypeptide, retinoic acid, nitric oxide, and sonic hedgehog as well as molecules derived from genes like the FBJ osteosarcoma oncogene and immediate early genes 14‐35 . Experimental investigations and clinical randomized trials have shown that atropine eye drops applied in low concentrations reduce the rate of myopization 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study, which are supported by observations made in a previous investigation, may suggest that EGF and members of the EGFR family, such as amphiregulin, are some of the substances that were positively or negatively associated with the development of experimental myopia in previous studies. These substances include dopamine, acetylcholine, and other molecules from the cholinergic system and GABAergic system, insulin, glucagon, glucagon‐like peptide‐1, basic fibroblast growth factor, transforming growth factor beta, vasoactive intestinal polypeptide, retinoic acid, nitric oxide, and sonic hedgehog as well as molecules derived from genes like the FBJ osteosarcoma oncogene and immediate early genes 14‐35 . Experimental investigations and clinical randomized trials have shown that atropine eye drops applied in low concentrations reduce the rate of myopization 35 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that citicoline significantly increased dopamine levels and synthesis rate in the striate Effects on the levels of other neurotransmitters have been reported by other authors [174][175][176][177][178]. The action of citicoline upon the dopaminergic system has also been studied by investigating its pharmacological actions in many experimental models [179][180][181][182][183][184][185][186][187][188][189][190][191][192][193]. Citicoline increases norepinephrine release [194], influences the relationship between glutamate and GABA [195], and increases the levels of vasopressin [196] and other pituitary hormones [197,198].…”
Section: Experimental Datamentioning
confidence: 97%
“…However, study published by Junfeng Mao et al showed that intraperitoneal injection of citicoline retarded the myopic shift induced by form deprivation in guinea pigs. 2 Another study published by Prachee Vasant Pawar et al showed that improvement in visual acuity with citicoline along with patching was significantly more than that with patching alone, in one year of treatment of amblyopia. 6 Many studies have shown neuro-protective effects of citicoline in glaucoma, amblyopia, non arteritic ischemic optic neuropathy, cerebral stroke, dementia, Parkinson's disease and many other diseases due to increase in dopamine levels in brain and protective effects of phosphatidylcholine in retinal as well as nerve ganglion cells.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic citicoline treatment leads to increase in dopamine receptor densities and promotes partial recovery of dopamine receptor functions (which normally decreases with aging). 2,3 Citicoline activates the biosynthesis of structural phospholipids (phosphatidylcholine) in neuronal cell membranes, thus an increased neurotransmitter levels and enhanced neuroprotection. 3,4 It stimulates glutathione synthesis and facilitates preservation of sphingomyelin, thus promoting signal transduction in nerve cells of retina.…”
Section: Mechanism Of Action Of Citicolinementioning
confidence: 99%
See 1 more Smart Citation